The procedure for preparing one-second variometer data of the Argentine Island geomagnetic observatory - Yurii Sumaruk; Mykhaylo Orlyuk; Andriy Marusenkov; Yurii Otruba (Ukrainian Antarctic Journal, 2024)
Magnetic observatories have been and continue to be basic elements for studying historical and contemporary changes in the Earth’s geomagnetic field. In most cases, satellite data are used to characterize and study rapidly evolving processes in near-Earth space. However, in recent decades, data from ground-based observatories have been used to support satellite missions. These data must have high temporal resolution to analyze rapidly changing processes. Furthermore, processed data from observatories should be delivered with minimal delay. Advances in technology now allow geomagnetic observatories to be equipped with high-resolution instruments, enabling the rapid delivery of final data. This paper outlines the methods developed to obtain one-second ImagCDF data of the Quasi-definitive level using the geomagnetic records of the Argentine Island observatory (INTERMAGNET code AIA). The observatory's state-of-the-art equipment and absence of anthropogenic noise produce results that meet the INTERMAGNET requirements. The primary data were validated by analyzing the distribution of instrumental errors in the absolutemeasurements. The quality of the difference in the field’s absolute value was assessed using statistical parameters, including the mean, standard deviation, and the absolute value of the maximum deviation. Peak and irregular noise values were identified by analyzing the results of numerical differentiation of the 10 Hz records from the LEMI-025N63 and the difference signals between this magnetometer and the proton magnetometer POS-1. Regular noises were identified from the signal spectra. Occasional spikes in the POS-1 readings were corrected by interpolating data between valid counts. One-minute temperature data of the sensor and electronic unit of the LEMI-025N63 variometer were aligned with the magnetic records (using identical digital filtering and resampling procedures). The data were processed using software recommended by INTERMAGNET.